Decoupled Estimation of 2D DOA for Coherently Distributed Sources Using 3D Matrix Pencil Method. (28th August 2008) - Gaoyi Gaoyi, Zhang Zhang; Bin Bin, Tang Tang
Abstract : A new 2D DOA estimation method for coherently distributed (CD) source is proposed. CD sources model is constructed by using Taylor approximation to the generalized steering vector (GSV), whereas the angular and angular spread are separated from signal pattern. The angular information is in the phase part of the GSV, and the angular spread information is in the module part of the GSV, thus enabling to decouple the estimation of 2D DOA from that of the angular spread. The array received data is used to construct three-dimensional (3D) enhanced data matrix. The 2D DOA for coherently distributed sources could be estimated from the enhanced matrix by using 3D matrix pencil method. Computer simulation validated the efficiency of the algorithm.